Recruitment of dendritic cells using 'find-me' signaling microparticles for personalized cancer immunotherapy. (March 2022) - Lee, Jae Ah; Shin, Jung Min; Song, Seok Ho; Kim, Chan Ho; Son, Soyoung; Shin, Sol; Park, Jae Hyung
Abstract: Therapeutic cancer vaccines have attracted attention because of their potential to prime cytotoxic T cells, which are highly antigen (Ag)-specific, allowing personalized cancer immunotherapy. However, because of their low immunogenicity, cancer vaccines have been used in only a few types of cancers in clinics, primarily because of the poor Ag presentation of dendritic cells (DCs). To address these limitations of cancer vaccines, we show that 'find-me' signaling polymeric microparticles (F-PMs) bearing tumor lysate as an Ag can efficiently recruit DCs and facilitate antigen presentation. When subcutaneously injected into tumor-bearing mice, F-PMs significantly increased mature DCs in tumor-draining lymph nodes by eliciting adenosine triphosphate (ATP)-induced chemotaxis, resulting in high antitumor efficacy. CD8 + cytotoxic T cells were remarkably enriched in the tumor microenvironment following co-administration of an immune checkpoint inhibitor with F-PMs. We demonstrated that F-PMs elicit a robust antitumor immune response, which may provide a promising therapeutic option for cancer treatment.